ADS-J1 disaggregates semen-derived amyloid fibrils. Issue 6 (29th March 2019) - Li, Jinqing; Yang, Zichao; Liu, Han; Qiu, Mengjie; Zhang, Tingting; Li, Wenjuan; Li, Zhaofeng; Qi, Tao; Qiu, Yurong; Li, Lin; Zhou, Xuefeng; Liu, Shuwen; et al.
Abstract : Semen-derived amyloid fibrils, comprising SEVI (semen-derived enhancer of viral infection) fibrils and SEM1 fibrils, could remarkably enhance HIV-1 sexual transmission and thus are potential targets for the development of an effective microbicide. Previously, we found that ADS-J1, apart from being an HIV-1 entry inhibitor, could also potently inhibit seminal amyloid fibrillization and block fibril-mediated enhancement of viral infection. However, the remodeling effects of ADS-J1 on mature seminal fibrils were unexplored. Herein, we investigated the capacity of ADS-J1 to disassemble seminal fibrils and the potential mode of action by applying several biophysical and biochemical measurements, combined with molecular dynamic (MD) simulations. We found that ADS-J1 effectively remodeled SEVI, SEM186–107 fibrils and endogenous seminal fibrils. Unlike epigallocatechin gallate (EGCG), a universal amyloid fibril breaker, ADS-J1 disaggregated SEVI fibrils into monomeric peptides, which was independent of oxidation reaction. MD simulations revealed that ADS-J1 displayed strong binding potency to the full-length PAP248–286 via electrostatic interactions, hydrophobic interactions and hydrogen bonds. ADS-J1 might initially bind to the fibrillar surface and then occupy the amyloid core, which eventually lead to fibril disassembly. Furthermore, the binding of ADS-J1 with PAP248–286 might induce conformational changes of PAP248–286 . Disassembled PAP248–286 might not be favorable to re-aggregate into fibrils. ADS-J1 also exerts abilities to remodel a panel of amyloid fibrils, including Aβ1–42, hIAPP1–37 and EP2 fibrils. ADS-J1 displays promising potential to be a combination microbicide and an effective lead-product to treat amyloidogenic diseases.